Optical soliton solutions to the Fokas-Lenells equation via sine-Gordon expansion method and (m plus (G?/G))-expansion method - Ismael, Hajar F.; Bulut, Hasan; Baskonus, Haci Mehmet (Indian Acad Sciences, 2020)
The purpose of this study is to find some novel soliton solutions of Fokas-Lenells (FL) equation where the perturbation terms are taken into account with nonlinearity. The sine-Gordon expansion method (SGEM) and the (m+(G '/G))-expansion method are used in this context. The dark, bright, dark-bright and singular optical soliton solutions are successfully obtained. Moreover, the constraint conditions for guaranteeing the existence of solutions are also given.
Keywords: Optical soliton solutions; Fokas-Lenells equation; sine-Gordon expansion method; (m plus (G'/G)) method